Tetramethylpyrazine Ameliorates Peritoneal Angiogenesis by Regulating VEGF/Hippo/YAP Signaling - Zhu, Xiaolin; Shan, Yun; Yu, Manshu; Shi, Jun; Tang, Lei; Cao, Huimin; Sheng, Meixiao (Frontiers in Pharmacology, 2021)
Angiogenesis of human peritoneal vascular endothelial cells (HPVECs), linked to vascular endothelial growth factor (VEGF)/VEGF receptor2 (VEGFR2) signaling, is a complication of peritoneal fibrosis (PF). Hippo/YAP signaling interacts with VEGF/VEGFR2 signaling, but the effect on peritoneal angiogenesis and PF has not been studied. We tested VEGF/Hippo/YAP inhibition by tetramethylpyrazine (TMP) in PF mice and HPVECs. This treatment ameliorated peritoneal dialysis (PD)-induced angiogenesis and PF. In mice, PF was associated with upregulation of VEGF, TMP ameliorated submesothelial fibrosis, perivascular bleeding and Collagen I abundance. In HPVECs, angiogenesis due to human peritoneal mesothelial cells (HPMCs)-conditioned medium, TMP alleviated HPVECs migration, tube formation and YAP nuclear translocation. PF mice and HPVECs were performed in YAP knockout to further confirm our finding. YAP deletion attenuated the PD-induced or VEGF-induced increase in angiogenesis and PF. The amount of CYR61 and CTGF significantly less in YAP-knockout group. To study the possibility that TMP could benefit angiogenesis, we measured the HPVECs migration and tube formation, and found both were sharply increased in YAP overexpression; TMP treatment partly abolished these increases. As well, the amount of VEGFR localized in the trans-Golgi network was lower by double immunofluorescence; VEGFR and its downstream signaling, including p-ERK, p-P38 and p-Akt were more in YAP overexpression. Overall, TMP treatment ameliorated angiogenesis, PF and peritoneum injury. These changes were accompanied by inhibition of VEGF/Hippo/YAP.